Ironwood/hophornbeam leaf rust, an emergent disease across the southeastern United States affiliated to Melampsoridium asiaticum - Anger, Nicolas; Held, Benjamin W.; Blanchette, Robert A.; Ono, Yoshitaka; Aime, Catherine M.; Smith, Jason A. (Frontiers in Forests and Global Change, 2023)
In the late fall of 2018, foliar rust (referred to as ironwood/hophornbeam leaf rust [IHLR]) was discovered in several counties in Florida, United States, on ironwood (Carpinus caroliniana) and hophornbeam (Ostrya virginiana), both members of the Betulaceae. Uredinia were observed on leaves and, in some cases, samaras of both species at numerous locations on trees of all age classes. Similar reports across the southeastern United States (Georgia, the Carolinas, Tennessee, and Texas) were detected the following year, with European hornbeam (Carpinus betulus) being reported as an additional host, while Ostrya virginiana var. guatemalensis in El Salvador was also discovered showing signs of uredinial infection. Field observations and analyses of morphological data obtained with light and scanning electron microscopy on IHLR and related Melampsoridium herbarium samples and combined molecular data from the ITS and LSU loci indicate that (i) IHLR across samples from the southeastern United States and El Salvador belong to the same taxon; (ii) IHLR is closely affiliated to M. asiaticum; and (iii) some taxonomic modifications might be necessary at the genus level. No alternative (gametophyte) host has been identified, and the rust is likely overwintering in the uredinial stage. This disease represents a novel leaf pathogen on these hosts in North America, and efforts are needed to monitor future disease epidemiology and impacts on these native and cultivated tree species.